La nuova sfida di SEAT Pagine Gialle - Landini, Leonardo (GEOmedia, 2008)
SEAT Pagine Gialle's new challenge SEAT Pagine Gialle is a company that for over 80 years has provided information services, search and communication tools. The companies success and notoriety is built on a customer base of about 20 million families and 3 million professional operators with a continually updated technology with which it integrates with detailed geographical information that allows it to reach millions of users every day. The services the company offers include an advanced cartographic web-based search, satellite and aerial photos, the calculation of driving instructions, weather forecasts and traffic information, 360 degree views and the modelling of whole cities in 3D.